Republic of Croatia : Staff Report for the 2004 Article IV Consultation and Request for Stand-By Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
This paper examines Croatia's 2004 Article IV Consultation and Request for Stand-By Arrangement (SBA). Croatia has established a record of solid growth and low inflation since the mid-1990s. Real GDP growth has averaged about 4.5 percent, with inflation in the low single digits. This performance compares well with the European Union-15 (EU-15) and other Central and Eastern European countries (CEECs). Structural reform has also advanced, and the private sector is vibrant. To support their policies for 2004-05, the authorities have requested a new 20-month SBA, which they intend to treat as precautionary.